PENGARUH TEKNIK PKC-KO TERHADAP KECERDASAN SOSIAL SISWA KELAS VIII SMP NEGERI 1 BENGKULU TENGAH - UMI FADILLAH (Psikodidaktika, 2017)
social intelligence implicated in positive cash terbinanya interpersonal interaction, where people are able to live in harmony and peace in the difference. (1) This study aims to determine social intelligence junior class VIII Negrei 1 Central Bengkulu given guidance layanna mengguankan group CCP-knockout techniques,. (2) Social intelligence eighth grade students of SMP Negeri 1 Central Bengkulu who have been given group counseling services do not use the CCP-knockout techniques. (3) The effect of PKC-knockout techniques to Social intelligence Junior High School eighth grade students of Central Bengkulu. This study using the quantitative approach to the experimental method withmodels Non Equivalent This study population is class VIII and VIII 4 5 SMP Negeri 1 Central Bengkulu. The research sample was determined bypurposive sampling using awith 20 students, 10 students of class VIII 4 and 10 Grade VIII 5. The instrument used was a questionnaire(questionnaire)the model skla Likert The validity of 0,367, the reliability 0.873. Data analysis techniques used in this research thattest the Mann-Whitney U with SPSS 20. The findings of this study show that: (1) Social intelligence level of students in the experimental group pre-tess is at a low average category with a score of 83 after by using the technique of group counseling services PKC-KO on the post-tess is at a high category with a score of 150. (2) Social Intelligence Level control group students in Pre-tess is at a low average category with a score of 85 after a given group counseling services are not using the technique of PKC-KO on the Post-tess middle category with a score of 114. (3) There is a significant effect of PKC-KO techniques against Social Intelligence Junior High School eighth grade students 1 Central Bengkulu. It is marked by a significant difference between students' Social Intelligence by Group Tutoring services using PKC-knockout techniques and not using CCP-knockout techniques.